Usability of intravenous thiamine injection test compared with odor stick identification test for Japanese patients with severe traumatic brain injury. Issue 2 (April 2020) - Yamaki, Tomohiro; Oka, Nobuo; Odaki, Masaru; Kobayashi, Shigeki
Abstract: Objective: Olfactory dysfunction is often observed after severe traumatic brain injury (sTBI). Its diagnosis is difficult because patients with sTBI have a communication disability following impaired consciousness and communication disorder. The intravenous thiamine injection (IT) test is one of the representative diagnostic examinations to identify dysfunction, and it is often used in medical certification for liability insurance of automobiles in Japan because it could be judged by a simple reaction. However, the extent of usefulness of the IT test in the diagnosis of olfactory dysfunction in patients with sTBI is unknown. In this study, we validated the usability of the IT test and compared the results with those of the odor stick identification test for the Japanese (OSIT-J) to evaluate the sensitivity of the IT test in patients with sTBI. Methods: The study enrolled 205 subjects, including 10 healthy volunteers and 195 patients with sTBI. First, we examined olfactory dysfunction in sTBI patients using OSIT-J. Subsequently, we performed the IT test among patients with olfactory dysfunction. Results: In the first part, 41 subjects, including 10 healthy volunteers, were examined by using the OSIT-J test. As a result, 28 patients were diagnosed with olfactory dysfunction (90.3%, p < 0.0001), including anosmia and parosmia, compared with healthy volunteers. Among the 12 odors, garlic odor was easily recognized for patients with olfactory dysfunction. As a consequence of the IT test for 11 patients with olfactory dysfunction, four patients recognized thiamine odor, and seven patients did not. All four patients could recognize the garlic odor of OSIT-J, but 2 of the seven patients could recognize the garlic odor of OSIT-J, suggesting that the thiamine odor is linked to garlic odor (p = 0.046), but not always. The detection rate of olfactory dysfunction through the IT test was 36.4%. Conclusion: Our data showed that garlic odor, which is similar to thiamine odor, was easily recognizable for patients with sTBI. However, the IT test might overlook the diagnosis of olfactory dysfunction because it only identifies one odor. In addition, thiamine frequently induces angialgia. We should pay attention to the overconfidence of the IT test for patients with sTBI.